BIMBINGAN TEKNIS PEMANFAATAN LIMBAH KULIT KOPI MENJADI BRIKET UNTUK KELOMPOK TANI KOPI - Mochammad Agung Indra Iswara; Asalil Mustain; Agung Ari Wibowo; Listiyana Candra Dewi; Ernia Novika Dewi; Rucita Ramadhana; Rofiq Hamzah (P3M Politeknik Negeri Malang, 2025)
Ketindan Village in Lawang Regency is a coffee plantation area where most of the residents work as coffee farmers. Using simple methods for harvesting, the area produces various types of coffee, such as Robusta, Arabica, and several types of fermented coffee. One of the challenges faced is the large amount of coffee husk waste generated during the coffee bean peeling process. This coffee husk waste is typically discarded, causing negative environmental impacts on the surrounding area. One solution to address this waste issue is by educating the local community and conducting practical workshops on how to make briquettes from coffee husk waste. The residents appear enthusiastic and receptive to the information on how to produce briquettes using coffee husks as the main material. With this educational effort, it is hoped that the community will be able to process coffee husk waste into useful products that generate high economic value.